A transferable energy model for determining the future energy demand and its uncertainty in a country's residential sector. Issue 6 (17th August 2020) - Martinez-Soto, Aner; Jentsch, Mark F.
ABSTRACT: Residential energy models are a common tool for determining the overall energy consumption attributed to the housing sector of a country as well as for projecting the future energy demand in relation to energy conservation policies. However, current residential energy models often require large amounts of input data, have a limited transferability to different countries and often fail to correctly depict trends in energy consumption. Furthermore, no current model gives an indication of the underlying uncertainties in its results. This paper presents a transferable residential energy model that combines statistical and building physics approaches and, with input data typically available in most countries, is able to model the annual and monthly residential energy demand of a given nation or region. In addition to providing trends in the residential sector's final energy demand according to area of use, the model also estimates uncertainties in the results in three probability bands at 30%, 60% and 90% confidence intervals. Results for a 'forecast period' 2001–2010 in three case study countries: Germany, Chile and the UK show a high overall agreement of the new modelling approach with the statistical data and the residential sector's energy consumption trends of these three countries.